The Risks and Benefits of Myopia Control - Bullimore, Mark A; Ritchey, Eric R; Shah, Sunil; Leveziel, Nicolas; Bourne, Rupert R A; Flitcroft, D Ian (Ophthalmology (Rochester, Minn.), 2021)
The prevalence of myopia is increasing around the world, stimulating interest in methods to slow its progression. The primary justification for slowing myopia progression is to reduce the risk of vision loss through sight-threatening ocular pathology in later life. The paper analyzes whether the potential benefits of slowing myopia progression by one diopter justify the potential risks associated with treatments. First, the known risks associated with various methods of myopia control are summarized, with emphasis on contact lens wear. Based on available data, the risk of visual impairment and predicted years of visual impairment are estimated for a range of incidence levels. Next, the increased risk of potentially sight threatening conditions associated with different levels of myopia are reviewed. Finally, a model of the risk of visual impairment as a function of myopia level is developed, and the years of visual impairment associated with various levels of myopia and the years of visual impairment that could be prevented with achievable levels of myopia control is estimated. Assuming an incidence of microbial keratitis between 1 and 25 per 10,000 patient years and that 15% of cases result in vision loss, leads to the conclusion that between 38 and 945 patients need to be exposed to five years of wear to produce 5 years of vison loss. Each additional diopter of myopia is associated with a 57%, 20%, 21%, and 30% increase in the risk of myopic maculopathy, open angle glaucoma, posterior subcapsular cataract, and retinal detachment, respectively. The predicted mean years of visual impairment ranges from 4.42 in a -3 D myope to 9.56 in a -8 D myope and a one diopter reduction would lower these by 0.74 and 1.22 respectively. The potential benefits of myopia control outweigh the risks: the number needed to treat to prevent 5 years of visual impairment is between 4.1 and 6.8 while fewer than 1 in 38 will experience a loss of vision as a result of myopia control.